The allergic phenotype during the first 10 years of life in a prospective cohort. Issue 3 (17th June 2019) - Björkander, Sophia; Hallberg, Jenny; Persson, Jan‐Olov; Lilja, Gunnar; Nilsson, Caroline; Sverremark‐Ekström, Eva
Abstract: Background: Heredity and environmental parameters jointly affect allergy development. Here, we used a Swedish prospective cohort to study the influence of heredity and factors usually associated with allergic disease and the development of allergic manifestations in combination with immunoglobulin E (IgE) sensitization at four different time points until 10 years of age. Methods: Parents‐to‐be were characterized concerning allergy and their children (n = 281) were divided based on allergic heredity and followed from birth and clinically examined for IgE‐associated allergic symptoms until 10 years of age. The relation between allergy and early‐life parameters was analyzed by logistic regression. Group‐wise comparisons were made by nonparametrical tests. Results: Early life eczema and/or asthma in combination with IgE sensitization, was a strong indicator of allergy at a later time point. Further, the early occurrence of multiple allergic symptoms among IgE‐sensitized children predisposed for a more complex allergic phenotype at later ages, independently of allergic heredity. At 10 years of age, allergic children had higher fractional exhaled nitrogen oxide (FeNO) levels, regardless of asthma, and FeNO levels were also influenced by heredity. Birth season was strongly associated with allergy development, but only in children with two allergic parents. Conclusion: Allergic eczema/asthma in early life, being born during the autumn/winter, having multiple allergic symptoms and two allergic parents were all strong predictors for having allergic diseases at 5 and 10 years of age. However, the allergic march seems to be independent of heredity, as IgE‐mediated allergies follow the same trajectories in children with and without allergic heredity. Abstract : Allergic eczema/asthma in early life, being born during the autumn/winter, having multiple allergic symptoms and two allergic parents were all strong predictors for having allergic diseases at 5 and 10 years of age. However, the allergic march seems to be independent of heredity, as IgE‐mediated allergies follow the same trajectories in children with and without allergic heredity.